2022
DOI: 10.21763/tjfmpc.992209
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19’un Gebelik, Doğum Öncesi Bakım ve Doğum Üzerindeki Etkileri

Abstract: Introduction:The research was carried out to determine the effects of the COVID-19 pandemic on pregnancy, antenatal care, birth planning and postpartum period. Methods: The descriptive cross-sectional study was conducted in November-December 2020 using a web-based online questionnaire. The population of the study consists of women received prenatal care from a state hospital in a province in the south of Turkey, attended childbirth preparation classes, and spent their pregnancy and delivery process during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In another study on the subject, it was reported that fear of COVID-19 was one of the barriers to receiving a full ANC service during the pandemic (Tadesse, 2020). In (Kaya Senol & Ucar, 2022). In a different study, 77.6% of pregnant women stated that they feared contracting coronavirus.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In another study on the subject, it was reported that fear of COVID-19 was one of the barriers to receiving a full ANC service during the pandemic (Tadesse, 2020). In (Kaya Senol & Ucar, 2022). In a different study, 77.6% of pregnant women stated that they feared contracting coronavirus.…”
Section: Discussionmentioning
confidence: 97%
“…Receiving antenatal care can be affected by various factors or care is not received or delayed. It was said that the COVID-19 pandemic heavily affected antenatal care (Fryer et al, 2020;Wu et al, 2020;Kaya Senol & Ucar, 2022;Nazik et al, 2022). For this reason, this study was performed to examine the fear of COVID-19 and the status of receiving ANC during the pandemic in the region where we live.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation